Social Exchange Use of Twitter Social Media and Adolescent Behavior Deviations (Bullying, Pornography and Free Sex) in the Kartini Area, Central Jakarta - Banua, Rochani; Sekarnigrum, Bintarsih; Pitoyo, Pitoyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study describes and analyses the process of adolescents' behaviour deviation in social exchange on Twitter social media. In reviewing this, the writer uses George C. Homans' social exchange theory which looks at the costs and rewards of an option. Teenagers choose information from social exchanges on social media Twitter based on costs and rewards. This choice that they will later apply to their lives in the form of behaviour, adolescent deviant behaviour is a form of sacrifice in using Twitter social media. This research is descriptive data collection techniques using interviews and field observations. The conclusion shows that social exchange in the use of Twitter social media is in the form of ideas and ideas that have a value of the benefit (reward) in the form of current information and sacrifice (cost) in the form of deviant behaviour in adolescents such as bullying, free sex and pornography.